Stapler Haemorroidopexy - our experience in a tertiary care hospital of central India - Anant Kumar Rakhonde; Roshan Chanchalani (International Journal of Medical Research and Review, 2015)
Background: Symptomatic haemorroids poses a very big issue on the public health. Treatment options for haemorroids is surgery for 2nd, 3rd , 4th degree haemorroids, but due to fear of surgery due to pain patients usually tries to avoid it and later on comes with complications which in turn adds for increased morbidity and mortality. Since stapler haemorroidopexy is claimed to be superior than other available procedures for heamorroids the study is undertaken to evaluate the efficacy in terms of operation time, post-operative pain, hospital stay, return to normal activity and return to work, relapse of symptoms, recurrence and patient satisfaction.Material and Methods: The Study was done using a circular stapling device for the treatment of Symptomatic haemorrhoids grade 2, 3 and 4 over a period from November 2011 to December 2014 for age group between 22 to 78 yrs of age.Observations: Total 88 patientswith symptomatic haemorroids who agreed for treatment with stapler surgery for haemorroids were operated. Operative time ranged between 55- 20 min.with mean operative time 36.44 min. Post-op pain measured using Visual analogue scale after aprox. 24 hrs and is in the range of mild pain(0-2) in 82 (93.18%) patients. Post-operative pain: In 4 (4.54%) patients were having VAS between 2-4 and required injection diclofenac sodium analgesic to be added for pain in the regime. 2 patients (2.27%) complaints of unbearable pain and opioid analgesic has to be added in such cases but for 2 days. Mean hospital stay ranges between 23 hrs -80hrs. All the 82 patients (93.18%) patients returned to normal activity within 4-5 days and joined their respective field of work within 7-8 days.Conclusion: Stapler haemorroidopexy is a good alternative to the open surgery for the treatment of 2nd, 3rd, and 4th degrees haemorrhoids in terms of less pain, early return to normal activities, faster return to work, but high cost of instrument puts the procedure to back foot